KEBIJAKAN PEMERINTAH REPUBLIK INDONESIA DALAM MENGATASI SITUS PORNO PADA MEDIA MAYA Studi Peran Departemen Komunikasi dan Informatika RI dalam Penyusunan Kebijakan Komunikasi Indonesian Government Policy in Overcoming Porn Sites in Cyber Media; A Role Study of Department Information and Technology In Arranging a Communication Policy - Rizky Ameliah Cawidu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2011)
AbstractThis research aims to find out what kind of policy in government has created through Depkominfo in overcoming pornsites in cyber media and how the government spreads the policy of public. The method of analysis used was descriptivequalitative analysis with data reduction, data presentation, and the conclusion of data from interview resulth. The unit ofanalysis were (the kinds of the existing government policies and the ones that would be issued, (2) InformationTechnology Era which was increasing either the policy which was directly issued by Depkominfo or the one issued byother departments as the team of policy makers. The effect of this policy would also be viewed from the aspects ofculture, religion, community’s mindset, technology, and economy. Teh result show that the policy issued byDepkominfo has positive value on Indonesia people and other countries. Even though it is late tohave policy ofInformation Technology and Telematika Law or Cyber Law, Indonesia already has a good point to pursue itsachievement. There are three things to do to eliminate pornography and porn sites; (a) self-control, (b) govermentregulations and policy, (c) collabortion with satellite operators and providers that exist in Indonesia. On the other hand,however, there are several inhibiting factors of the policy such as inadequate technology expert and software which canbe hacked by the hackers. From the economic point of view, the elimination of porn sites by Indonesian governmentwill threat some segments in Indonesia.